Dynamics of a power hacksaw mechanism, contact interaction with the workpiece, and material removal. (2nd January 2022) - Maini, Aman Kumar; Vaz, Anand; Dauphin-Tanguy, Geneviève
ABSTRACT: During the metal cutting process, dynamics of a mechanism influence the cutting phenomenon at the contact interface while the contact interaction also has its reciprocal effect on the mechanism. Modeling the dynamics and the contact interaction between the cutting tool and workpiece, causing material removal, is a complex and challenging task. The mechanism of a machine involves a number of interconnected rigid bodies that interact with each other dynamically. Modeling dynamics of such mechanisms is necessary from the point of view of design and analysis. In this paper, the multibond graph approach has been used fxor modeling the dynamics of a power hacksaw machine. The power hacksaw machine is quite commonly used for cutting materials in industries. This graphical approach offers scope for analysis of causality, which is an important aspect of physical systems, and its application, a feature not offered by the energy-based formulations, such as the Euler-Lagrange's method and Hamilton's method. These energy-based formulations, commonly used for modeling dynamics of physical systems, also tend to be too mathematically inclined. MATLAB coding for simulation has been done directly from the multibond graph model without explicitly deriving system equations. The simulation results have been presented, analyzed, and discussed.